Perancangan Sistem Informasi Inventaris Barang Laboratorium Komputer SMPN 11 Kota Bengkulu - Lediwara, Nadiza; Rivaldi, Muhammad (Program Studi Teknik Informatika Universitas Pamulang, 2019)
SMPN 11 Bengkulu City used the system manually for several years to handle activities such as data collection and inventory reports. It caused the frequent occurrence of goods scattered, sometimes damaged goods were not recorded, the occurrence of data redundancy, so that errors often occured in data collection and calculation. The aim of this research is to build a website-based inventory information system that can minimize data redundancies and errors in calculations and data collection. The methodology used in making this system uses the waterfall method, UML diagrams, database design, and interface design. The results of this research are web-based information systems. The development of the system indicates that this system has the potential to support the activities of processing inventory data automatically, quickly and accurately.